A midwifery-led prevalence programme for caesarean section surgical site infections. (March 2021) - Baxter, E.
Summary: Caesarean section (CS) is a common procedure accounting for 29% of all deliveries. Surgical site infections (SSI) are a risk with any surgical procedure. A CS SSI prevalence programme led by a midwife, who is also an infection prevention and control matron, was implemented to determine the rate of CS SSI within the trust. The initial CS SSI rate was 26% over a 3-month period (June–August 2012). Targeted interventions were put in place to reduce the CS SSI rate, and by 2019, it had decreased to 8%. Hospitals should consider implementing CS SSI surveillance and prevention programmes. Real benefits can be realized with minimal resources.